Japan's long stagnation, deflation, and abenomics : Mechanisms and lessons - Aramaki, Kenji (Palgrave Macmillan, 2018)
The book examines Japan's prolonged economic stagnation and deflation since the 1990s, and evaluates the policies of Abenomics. Aramaki analyzes macroeconomic challenges, structural reforms, and their implications for Japan's recovery and future growth